Green and Efficient Synthesis, Spectroscopic, Characterization, Antibacterial Activity of Some Selected Transition Metal Complexes of Novel Schiff Base Ligand Derived from 2-amino 5-methyl benzimidazole with 2-bromo Isophthalaldehyde - Sadashiv N. Sinkar,; Ram. B. Kohire,; Dnyaneshwar T. Nagre, (International Journal of Scientific Research in Science and Technology, 2024)
A Green and efficient environmentally synthesis using scientific microwave method of novel ligand derived from 2-amino 5-methyl benzimidazole with 2-bromo Isophthalaldehyde. Metal complexes were derived from Mn(II) chloride and nitrate of Co(II), Ni(II), Cu(II), Zn(II), Cd(II), salts with novel ligand at the end of the reaction all metal complexes show fine colour. By TLC and melting point of each complex was confirming the formation of metal complex. Characterization of novel ligand carried out by elemental analysis, IR,1HNMR, Mass spectroscopy and characterization of metal complexes carried out by UV, IR. The thermal stability of Zn (II) and Cd (II) complexes was studied by thermo-gravimetric analyses (TGA). All metal complexes show antibacterial activity against E-Coli, S.Aureus and S.Typhi.
Keywords: Green Synthesis; Schiff base; Thermal Analysis; Antibacterial activity